Publisher Correction: Fluid-driven metamorphism of the continental crust governed by nanoscale fluid flow. Issue 1 (January 2019) - Plümper, Oliver; Botan, Alexandru; Los, Catharina; Liu, Yang; Malthe-Sørenssen, Anders; Jamtveit, Bjørn
In this Article, owing to a technical error, the Greek letter μ is missing from the scale bar measurements given in the caption for Fig. 2b-e; they appear as '50 m (b); 20 m (c); 1 m (d); 1 m (e)', but should be '50 μm (b); 20 μm (c); 1 μm (d); 1 μm (e)'. We apologize for this error and any confusion caused.